Studi Konsentrasi Larutan KOH dan Arah Orientasi Serat Rami terhadap Kekuatan Impak Komposit dengan Matrik Polyester - Pramitasari, Retno Eka; Irfa'i, Mochamad Arif; Prasetyo, Reza (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2021)
The development of increasingly advanced technology, especially in the health sector, can lead to an increase in the need for composite materials used. This study aims to describe the results of the concentration of KOH solution and the orientation of the ramie fiber on the impact strength of composites with a polyester matrix. This research is an experimental study with the manipulation variables are the concentration of the KOH solution and the orientation of the fiber direction by determining the value of the impact strength as the dependent variable of ramie fiber as a control variable of this study. This study obtained the optimum impact test result of 0.0711 J/mm2 with 5% KOH solution concentration and located at 0o/45o/90o fiber direction orientation. While the results of the lowest impact test resulted in a value of 0.0101 J/mm2 without soaking the KOH solution and located at 90o/0o/90o fiber direction orientation.